Becoming more sedentary? Changes in recovery positions of Mallard Anas platyrhynchos ringed in the Camargue, France, over the last 50 years - Guillemain, Matthieu; Champagnon, Jocelyn; Massez, Gregoire; Pernollet, Claire A.; George, Thierry; Momerency, Andre; Simon, Geraldine (Wildfowl, 2015)
Earlier studies from central and northern Europe have found a shortening of the ring recovery distance in Mallard Anas platyrhynchos, which was generally attributed to climate change leading to a northwards shift of the wintering range. Here we show that recovery distances for Mallard ringed during winter in the Camargue (southern France), at the southern end of their range, have also shortened over the last 50 years, from a mean of 417 km (s.e. ± 17.4) for birds ringed between 1950–1978 to 74 km (± 28.9) for birds ringed between 2002–2013. In contrast to the studies in other areas, however, the more recent recoveries of Mallard ringed in the Camargue were made to the south and west of where they were previously, and changes in ring recoveries were likely caused by a greater proportion of sedentary birds among the Camargue wintering population. Discarding unlikely methodological biases that may explain the pattern observed, we suggest three non-mutually exclusive hypotheses to explain such a change: a) increased attractiveness of Camargue habitats as a winter quarter, with migrant birds now staying for longer periods and allowing more local recoveries, b) hybridization between resident captive-bred and wild Mallards, and c) former migrants from northern Europe now foregoing long migration to this distant winter quarter due to climate change. Future studies combining genetic and isotope analyses may help in teasing these hypotheses apart, to provide a better understanding of the factors leading to such increased sedentarity.